Siberian Society and All-Russian Constituent Assembly in context of crisis of 1917 revolution - V. I. Vtorushin (Омский научный вестник: Серия "Общество. История. Современность")
Research objective is identification of the reasons of failure of process of legitimation of the Constituent assembly in development of the Russian revolution. The article considers as well as the problem of attitude of the Russian political parties to Institute of all-Russian Constituent Assembly and the reasons for the failure of the process of legitimizing of this Constituency in the development of the Russian revolution, the specifics of the election campaign in the Siberian region of the country and its outcomes as well as the reaction of the Siberian community at the dissolution of the constitutional forum of revolutionary Russia